2009
DOI: 10.1590/s0100-204x2009000900016
|View full text |Cite
|
Sign up to set email alerts
|

Fixação biológica de nitrogênio em cultivares de feijão-caupi recomendadas para o Estado de Roraima

Abstract: Resumo -O objetivo deste trabalho foi avaliar a fixação biológica de nitrogênio (FBN) em cinco cultivares de feijão-caupi: BR 17 Gurguéia, BRS Guariba, BRS Mazagão, UFRR Grão Verde e Pretinho Precoce 1. Em 2007, foram conduzidos um experimento em casa de vegetação e outro em campo, em esquema fatorial com cinco cultivares de feijão-caupi e quatro fontes de nitrogênio: adubação com ureia (50 kg ha -1 de N), inoculação com a estirpe de Bradyrhizobium BR 3262 ou BR 3267 e um controle absoluto. Aos 35 dias após a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
4
12
0
19
Order By: Relevance
“…These soil conditions indicate that a competing community established in the soil exists with the ability to nodulate velvet bean in low numbers (390 cells of rhizobia g soil -1 , as shown in Table 1). There was no nodulation from any of the applied nitrogen fertilization doses under greenhouse and field conditions, which was also observed by Melo and Zilli (2010) for five cowpea (Vigna unguiculata) plants. Inoculation with all strains promoted a higher SNC than did the native treatment, except for the plants inoculated with T3.16N and C4.8A.…”
Section: Greenhouse Conditionssupporting
confidence: 59%
“…These soil conditions indicate that a competing community established in the soil exists with the ability to nodulate velvet bean in low numbers (390 cells of rhizobia g soil -1 , as shown in Table 1). There was no nodulation from any of the applied nitrogen fertilization doses under greenhouse and field conditions, which was also observed by Melo and Zilli (2010) for five cowpea (Vigna unguiculata) plants. Inoculation with all strains promoted a higher SNC than did the native treatment, except for the plants inoculated with T3.16N and C4.8A.…”
Section: Greenhouse Conditionssupporting
confidence: 59%
“…They found that BR 3267 has the lowest performance for the number of nodules in relation to the other strains studied. Differing data was found by Melo and Zilli (2009) in a greenhouse experiment, where a greater number of nodules and nodule dry weight were seen in plants inoculated with the BR 3267 strain, compared to those inoculated with BR 3262.…”
Section: Resultsmentioning
confidence: 86%
“…O emprego da fixação biológica de nitrogênio (FBN), através da associação das leguminosas e bactérias diazotróficas simbiontes, denominadas de rizóbios, tem baixo custo e eleva a produção das plantas de feijão-caupi (MARTINS et al, 2003;RUMJANEK et al, 2005;ZILLI et al, 2006;GAULTER et al, 2008;ZILLI, 2009). Em Roraima, o uso de inoculante na cultura do feijão-caupi ainda é pouco utilizado.…”
Section: Introductionunclassified